Income of Order-oriented Medical Graduates and General Clinical Graduates: a Longitudinal Comparative Study - ZHANG Baisong, WANG Ziyue, HU Dan, LI Mingyue, WANG Huijuan, WEI Tiantian, CHENG Xiaoran, CHENG Haozhe, LIU Xiaoyun (Zhongguo quanke yixue, 2023)
Background The free training for rural order-oriented medical students has trained a large number of primary health personnel for the central and western regions of China. By the summer of 2021, the first order-oriented medical graduates had completed their compulsory service and face the choice of staying or leaving. The income is an important influencing factor of their choices, however, there are still few studies on the income of order-oriented medical graduates. Objective The panel data of order-oriented medical graduate cohort study was used to compare and analyze the change trend of the income of order-oriented medical graduates and general clinical graduates in the early career, and to explore the influencing factors of the change of income. Methods Qinghai University, Guangxi Medical University, Jiujiang Medical University and Gannan Medical University were selected to establish the order-oriented medical graduate cohort every year from 2015 to 2019, matching the general clinical graduates of the same grade as controls. The baseline survey was conducted, including basic information and family information. A total of four follow-up surveys were conducted in 2016, 2017, 2018 and 2020, including the status of standardized resident training (hereinafter referred to as "standardized training") , passing of medical licensing examination, working conditions and other information. Fixed effects model was used to explore the factors influencing the income of order-oriented medical graduates and general clinical graduates, and propensity score matching (PSM) was used to test the stability of the results. Results In the first two years after graduation, the income of order-oriented medical graduates was higher than general clinical graduates, and the difference was statistically significant (P<0.05) . Two years after graduation, the income of order-oriented graduates was lower than general clinical graduates, and the difference was statistically significant (P<0.05) . The results of the fixed effects model showed that completion of standardized training, passing of the medical licensing examination, working position, and year of graduation were factors influencing the income of order-oriented graduates (P<0.05) . The income of order-oriented graduates who completed the standardized training decreased by 47%, and the income of the graduates who passed the medical licensing examination and promoted increased by 16% and 10%, respectively; the income of the graduates in the third, fourth and fifth years after graduation increased by 7%, 16% and 34%, respectively, compared with the first year of graduation. Job change and graduation years were the factors influencing the income of general clinical graduates (P<0.05) ; Job change increased the income of general clinical graduates by 15%, and the income of graduates in the third, fourth and fifth year after graduation increased by 27%, 83% and 101%, respectively, compared with the first year. The regression results of two-way fixed effects model showed that the completion of standardized training, passing of the medical licensing examination, job change, staffing and graduation years had different effects on the income of order-oriented graduates and general clinical graduates (P<0.05) . The regression results of two-way fixed effects model using the data after PSM showed similar to the results of the original sample with good consistency. Conclusion The starting point of income of order-oriented graduates is higher, but the growth rate is significantly lower than general clinical graduates, the income gap between them has been increasing year by year. The main reasons include the loss of training allowance after the standardized training of order-oriented graduates and the income difference caused by different working institutions. At the same time, the income of order-oriented graduates decreases with the increase of graduation time, which will seriously affect their performance and willingness of primary care.